ALAM DAN KAUSALITAS DALAM KOSMOLOGI AL-GHAZALI - Syafa‘atul Jamal (DIRASAT: Jurnal Studi Islam dan Peradaban, 2018)
In the Islamic intellectual tradition, the concept of necessity of cause and effect in an event is different from the Western paradigm. In fact, it has been recorded very clearly in a lengthy discussion between al-Ghazali and several other philosophers, such as al-Farabi, Ibn Sina or Ibn Rusyd. Al-Ghazali doubted the theory by asking a few questions; like is it true that causality is causal ? Or is every fact in this theory must and must happen. If this is so, will this be the true fact of an event? This study is a type of library, trying to explore al-Ghazali’s views concerning the concept of causality in one of his major works, "Tahāfut al-Falāsifah.”